Quantitative easing, safe asset scarcity and bank lending - Johannes Tischer (Deutsche Bundesbank, 2021)
The Eurosystem's Public Sector Purchase Programme (PSPP) increased the scarcity of safe assets, which caused significant declines and substantial dispersion in European repo rates. However, banks holding these safe assets benefited from this development: First, using the German security register, this paper shows that scarcity affects bank funding costs, as their collateral supply is determined by their ex ante securities holdings and repo rates. Second, it makes use of the German credit register to show that asset scarcity had real effects: Banks more exposed to asset scarcity increased their credit supply.
Keywords: E51; E58; G11; G21; 330; Quantitative easing; safe asset scarcity; repo rates; bank lending; monetary transmission